Study of the mechanical properties of low carbon content HSLA steels - Illescas, S.; Fernández, J.; Asensio, J.; Sánchez-Soto, M.; Guilemany, J. M. (Revista de Metalurgia, 2009)
Two high strength low alloy steels (HSLA) with the same bulk composition and slight microalloying content differences were studied. The main purpose of the study was to determine the effect of different heat treatments and the influence of vanadium (V) on the microstructure and mechanical properties of the bainite present in each steel. For that purpose, standard tests were conducted to determine the hardness, toughness, tensile and yield stress of the different bainite-acicular ferrite structures found in both steels. The results show how the V content promoted the formation of acicular ferrite, resulting in a decrease in hardness and tensile strength while improving toughness.